Peran Konsultan Pajak Dalam Penyusunan dan Pelaporan SPT Tahuunan Serta SPT Masa Wajib Pajak - Aliyya Miya Savitri; I Made Suidarma (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the role of tax consultants in assisting taxpayers in fulfilling their tax obligations, particularly regarding the filing of Annual and Periodic Tax Returns (SPT). The research employed a qualitative descriptive method with a field study approach through direct observation and interviews during the internship program at IBU Consulting. The findings reveal that many taxpayers face difficulties in understanding tax regulations and procedures, making the assistance of tax consultants essential. Tax consultants act as a bridge between taxpayers and tax regulations by calculating tax liabilities, preparing returns, ensuring timely submission, and providing adequate tax education. This role not only helps taxpayers avoid penalties but also promotes better tax compliance and a more orderly tax system. The results emphasize the strategic role of tax consultants as key partners for taxpayers in the era of digital tax administration.